Antibacterial Bilayered Skin Patches Made of HPMA and Quaternary Poly(4-vinyl pyridine) - Isoglu, I. Alper; Demirkan, Cemre; Seker, Mine Gul; Tuzlakoglu, Kadriye; Isoglu, Sevil Dincer (KOREAN FIBER SOC, 2018)
This study aimed to produce poly(4-vinyl pyridine) and hydroxypropyl methacrylamide (HPMA)-based bilayer wound dressings materials enhancing healing mechanism for the wounds which have self-healing problem and high infection risk. These materials were designed to protect wound from secondary traumas caused microorganism invasion and do not have toxic substance release problem. Synthesis of quaternary poly(4-vinyl pyridine) (poly(Q4-VP)) which is the antibacterial layer of wound dressing material was carried out in two stages. At first stage, poly(4-vinyl pyridine) polymer was synthesized from 4-vinyl pyridine monomer by free radical polymerization. Then, poly(Q4-VP) was synthesized from poly(4-VP) by alkylation reaction with 6-bromocaproic acid. Resulted polymer was structurally characterized by FT-IR. The macroporous spongy structure, as the lower layer of wound dressing material, was prepared by cryogelation of HPMA. Then, the antibacterial polymer was electrospun onto the cryogel structure and bilayered material was obtained. Cryogel structure, fiber morphology and layer integration was examined by SEM. In order to enhance wound healing process, ascorbic acid (vitamin C) was loaded to cryogel layer and release was followed by spectrophotometrically. The antimicrobial properties of the materials were examined against Escherichia coli, Staphylococcus aureus and Candida albicans, respectively. According to the results, bilayered, antibacterial and antifungal against Staphylococcus aureus and Candida albicans, temporary wound dressings which can stimulate wound healing and have high swelling capacity were obtained successfully.
Keywords: Antibacterial wound dressings; Quaternary poly(4-vinyl pyridine); Electrospinning; Cryogel; COPOLYMERS; SCAFFOLDS; SURFACES; Materials Science; Polymer Science